2013
DOI: 10.37334/eras.v4i3.86
|View full text |Cite
|
Sign up to set email alerts
|

Symbols and Signs in Islamic Architecture

Abstract: Throughout history, Islamic signs and signification were recognized and appreciated by both Muslim and Non-Muslim scholars. The Islamic style of architecture is not only used in mosques, but also in other Islamic buildings and even in gardens. The architecture encompasses both secular and religious artistic styles. The aim of this study is to contextualize the concept of Islamic architecture. It seeks to make the readers appreciate the heritage of Islamic architecture, and to clarify on misconceptions about Is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…The Umayyad Mosque in Damascus used the shape of palm trees, pears, acanthus, and grape leaves in the ornamentation elements. While, abstracted shapes that applied associated with geometric lines in their composition, which is known as Arabesque [4,[7][8][9]. The abstraction process of floral ornaments may use geometric shapes to define the space and produce complex designs of ornaments (Figure 1-A) [8].…”
Section: Floral and Organic Ornamentsmentioning
confidence: 99%
See 3 more Smart Citations
“…The Umayyad Mosque in Damascus used the shape of palm trees, pears, acanthus, and grape leaves in the ornamentation elements. While, abstracted shapes that applied associated with geometric lines in their composition, which is known as Arabesque [4,[7][8][9]. The abstraction process of floral ornaments may use geometric shapes to define the space and produce complex designs of ornaments (Figure 1-A) [8].…”
Section: Floral and Organic Ornamentsmentioning
confidence: 99%
“…While, abstracted shapes that applied associated with geometric lines in their composition, which is known as Arabesque [4,[7][8][9]. The abstraction process of floral ornaments may use geometric shapes to define the space and produce complex designs of ornaments (Figure 1-A) [8]. The floral type is formed by the extension of elementary units by symmetrical repetition to create harmonious and balanced interior design elements (Figure 1-B) [10].…”
Section: Floral and Organic Ornamentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Behnam Ghasemzadeh, in his research on symbols and signs in Islamic architecture, concluded that the style in Islamic architecture includes both secular and religious artistic styles. The most common styles are calligraphy, geometry, and flower designs, which show a high degree of complexity [8]. In his research on integrated architectural theory for Islamic architecture, Sabir Numan proposed a theoretical model in the form of four integrated elements used to guide the design process in Islamic architecture.…”
mentioning
confidence: 99%